Opacity and the closet : queer tactics in Foucault, Barthes, and Warhol - De Villiers, Nicholas (University of Minnesota Press, 2012)
Opacity and the Closet interrogates the viability of the metaphor of "the closet" when applied to three important queer figures in postwar American and French culture: philosopher Michel Foucault, literary critic Roland Barthes, and pop artist Andy Warhol. Nicholas de Villiers proposes a new approach to these cultural icons that accounts for the queerness of their works and public personas.